PERSEPSI SISWA SMK TERHADAP KOMPETENSI PRAKTEK LAPANGAN KEPENDIDIKAN MAHASISWA TATA RIAS DAN KECANTIKAN FPP UNP - Ramadhani, Suci (rc-institut, 2019)
This research intent to describe the perceptions of vocational high school students on the competence of educational field practice students in the cosmetology and beauty department of the tourism and hospitality faculty of Padang State University. This research gets quantitative descriptive character. Total population 80 students and samples as much 80 students with samples taking tech it total sampling. Data analysis tech utilize percentage formula. Acknowledged observational result perception of vocational high school students on the pedagogic competence of educational field practice students in the cosmetology and beauty department of the tourism and hospitality faculty of Padang State University in a fairly good category with a percentage of 78%. Next perception of vocational high school students on the personality competence of educational field practice students in the cosmetology and beauty department of the tourism and hospitality faculty of Padang State University in a good category with a percentage of 83%. Next perception of vocational high school students on the social competence of educational field practice students in the cosmetology and beauty department of the tourism and hospitality faculty of Padang State University in a good category with a percentage of 85%. Meanwhile perception of vocational high school students on the professional competence of educational field practice students in the cosmetology and beauty department of the tourism and hospitality faculty of Padang State University in a good category with a percentage of 81%. From the results of descriptive analysis it can be seen that the perception of vocational high school students on competence of educational field practice students in the cosmetology and beauty department of the tourism and hospitality faculty of Padang State University in a good category with a percentage of 81,75%.